Small but Significant Errata/Typos in the Paper “The Distinction Between False Dilemma and False Disjunctive Syllogism” - Taeda Tomic (Informal Logic)
In the paper The Distinction Between False Dilemma and False Disjunctive Syllogism, by Taeda Tomić, Informal Logic vol. 41, No 4 (2021), pp. 607-639, there are typos in Figure 12, on page 630.